2015
DOI: 10.1002/adom.201400562
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and Photostimulated Red Emission in CaS:Eu2+,Dy3+ Nanophosphors

Abstract: The persistent and near-infrared photostimulated optical properties of CaS nanoparticles and CaS:Eu 2+ and CaS:Eu 2+ ,Dy 3+ nanophosphors are presented. Proposed mechanisms are elucidated for both phenomena by carrying out wavelength-resolved, thermally stimulated luminescence (TSL) and photostimulated luminescence (PSL) measurements. After UV (254 nm) irradiation, blue persistent and near-infrared photostimulated luminescence is obtained due to the presence of intrinsic defects in CaS nanoparticles. By introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 27 publications
(22 reference statements)
9
89
1
Order By: Relevance
“…Recently, Rodríguez Burbano et al reported that this material also exhibits OSL under illumination with infrared light [16]. Therefore, the sample was illuminated with 970 nm infrared light after measuring the initial afterglow.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Rodríguez Burbano et al reported that this material also exhibits OSL under illumination with infrared light [16]. Therefore, the sample was illuminated with 970 nm infrared light after measuring the initial afterglow.…”
Section: Resultsmentioning
confidence: 99%
“…The phase purity of both phosphors was verified by powder X-ray (Cu Kα) diffraction measurements using a Siemens D5000 diffractometer. Details concerning the synthesis, characterization and structural properties of the CaS:Eu nanophosphor were described by Rodríguez Burbano et al [16]. The phosphors were incorporated into a polymer layer by mixing an appropriate amount of the powders in a 20 wt% solution of kraton FG1901X in 3:1 toluene-to-methyl ethyl ketone, after which the mixture was cast on a circular glass plate with a diameter of 18 mm [42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods for determining the 5d-CB separation, such as using the charge transfer to a trivalent RE ion, can be more accurate. [ 19,28 ] However, the fi ts to the thermal quenching data give the qualitative indication that the 5d states of SLA are further separated from the CB than those of SMS. The source of SLA's temperature stability seems clear, the 5d states are well separated from the edge of the conduction band.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 93%
“…[4] Specifically,aCaS:Ce 3+ phosphor has been documented as an efficient green phosphor for white light-emitting diode (LED) because the absorption of Ce 3+ ion in the CaS lattice is in the blue region of the spectrum which matches well with the emission of aGaN blue LED chip. [4] Specifically,aCaS:Ce 3+ phosphor has been documented as an efficient green phosphor for white light-emitting diode (LED) because the absorption of Ce 3+ ion in the CaS lattice is in the blue region of the spectrum which matches well with the emission of aGaN blue LED chip.…”
mentioning
confidence: 98%